MODERNIZATION OF WORKING BLADES OF THE CONSTRUCTION GLASS SHELL MIXING DEVICE (Conferencea, 2022)
In the article " KVARTS " JSC of the enterprise mixing of glass fillers in the raw materials shopAn improved design of the apparatus with high efficiency, energy saving, changed shape of shovels and slope angles was proposed.